2021
DOI: 10.3390/molecules26216326
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Alkaline Exchange Membrane Water Electrolysis and Electrode Manufacturing

Abstract: Water electrolysis to obtain hydrogen in combination with intermittent renewable energy resources is an emerging sustainable alternative to fossil fuels. Among the available electrolyzer technologies, anion exchange membrane water electrolysis (AEMWE) has been paid much attention because of its advantageous behavior compared to other more traditional approaches such as solid oxide electrolyzer cells, and alkaline or proton exchange membrane water electrolyzers. Recently, very promising results have been obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 135 publications
0
38
0
4
Order By: Relevance
“…Li et al in a recent review distinguished between the durability-limiting factors for water-fed and concentrated KOH-fed AEMWEs, which among others included ionomer poisoning, ionomer detachment, and instability of the AEM. Alternative electrode-fabrication methods that exclude the use of an AEI in the catalyst layer are being reported more frequently, and such studies for AEMWE cells were recently reviewed by López-Fernández et al The relevant AEMWE studies, which reported performance measurements for a minimum of 100 h, are listed in Table and discussed further in section . These include reports for a unified electrode design where the catalyst layer was integrated within the GDL in a single component by means of growing the OER catayst directly on the substrate, such an Ni foam. , …”
Section: Membrane Electrode Assemblymentioning
confidence: 99%
“…Li et al in a recent review distinguished between the durability-limiting factors for water-fed and concentrated KOH-fed AEMWEs, which among others included ionomer poisoning, ionomer detachment, and instability of the AEM. Alternative electrode-fabrication methods that exclude the use of an AEI in the catalyst layer are being reported more frequently, and such studies for AEMWE cells were recently reviewed by López-Fernández et al The relevant AEMWE studies, which reported performance measurements for a minimum of 100 h, are listed in Table and discussed further in section . These include reports for a unified electrode design where the catalyst layer was integrated within the GDL in a single component by means of growing the OER catayst directly on the substrate, such an Ni foam. , …”
Section: Membrane Electrode Assemblymentioning
confidence: 99%
“…Nowadays, MEA fabrication occurs through deposition, coating, or embedded electrode methods, and these are just some of the options that have been investigated and completely inherited from more the mature PEM-WE technology. [144] In the current status of MEA fabrication, the appropriate combinations of electrocatalyst, ionomer, and membrane must be studied and optimized in order to improve the ionic conductivity through the electrodes. While this option might be considered for diluted KOH or K 2 CO 3 operation, alternatives need to be adopted for operation in pure water, which is a difficult challenge to overcome.…”
Section: Membrane Electrode Assemblymentioning
confidence: 99%
“…The integration of the electrocatalyst in the catalytic layer and in the MEA is critical for performance and durability improvements, but also critical to allow switching from dilute KOH or K 2 CO 3 to water feed in the near future. Nowadays, MEA fabrication occurs through deposition, coating, or embedded electrode methods, and these are just some of the options that have been investigated and completely inherited from more the mature PEM‐WE technology [144] . In the current status of MEA fabrication, the appropriate combinations of electrocatalyst, ionomer, and membrane must be studied and optimized in order to improve the ionic conductivity through the electrodes.…”
Section: Membrane Electrode Assemblymentioning
confidence: 99%
“…Recently, the study of anion exchange membrane water electrolysis (AEMWE) has been rapidly expanding as a new water electrolysis method to solve the issues of AWEs and PEMWEs. [11][12][13][14][15][16] AEMWE does not require highly concentrated alkaline solutions or noble metal catalysts, thereby reducing the environmental burden and material costs. Furthermore, they are expected to operate at higher current densities in more compact system sizes than conventional AWEs.…”
Section: Introductionmentioning
confidence: 99%